Erythromycin loaded by tetrahedral framework nucleic acids are more antimicrobial sensitive against Escherichia coli (E. coli) - Sun, Yue (Bioact Mater, 2021)
Erythromycin is a commonly used broad-spectrum antibiotic, but resistance to this antibiotic makes its use less effective. Considerable efforts, beside finding alternatives, are needed to enhance its antimicrobial effect and stability against bacteria. Tetrahedral framework nucleic acids (tFNAs), a novel delivery vehicle with a three-dimensional nanostructure, have been studied as a carrying platform of antineoplastic drugs. In this study, the use of tFNAs in delivering erythromycin into Escherichia coli (E. coli) was investigated for the first time. The tFNAs vehicle increased the bacterial uptake of erythromycin and promoted membrane destabilization. Moreover, it increased the permeability of the bacterial cell wall, and reduced drug resistance by improving the movement of the drug across the membrane. The tFNAs-based delivery system enhanced the effects of erythromycin against E. coli. It may therefore provide an effective delivery vehicle for erythromycin in targeting antibiotic-resistant bacteria with thick cell wall.